If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12w + -10 = 2(6w + -5) Reorder the terms: -10 + 12w = 2(6w + -5) Reorder the terms: -10 + 12w = 2(-5 + 6w) -10 + 12w = (-5 * 2 + 6w * 2) -10 + 12w = (-10 + 12w) Add '10' to each side of the equation. -10 + 10 + 12w = -10 + 10 + 12w Combine like terms: -10 + 10 = 0 0 + 12w = -10 + 10 + 12w 12w = -10 + 10 + 12w Combine like terms: -10 + 10 = 0 12w = 0 + 12w 12w = 12w Add '-12w' to each side of the equation. 12w + -12w = 12w + -12w Combine like terms: 12w + -12w = 0 0 = 12w + -12w Combine like terms: 12w + -12w = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -4(y-2y)+4=-6(2y-y)+3+9y | | 4a-12=-16 | | -2z-8=0 | | 4x^2+72=0 | | 0.6(x+70)+0.4x=67 | | -7w-20=-(7w+7) | | 5(a-8)+17=3(a-5) | | (3x+1/2)-(7x-41/2) | | 4[x-2]=24 | | 8x-10=-202 | | (y/3)^2=49 | | -12x-12=252 | | -2-4(-4z-3)=-5(-7z-1)-6 | | 3xy+4y=8 | | 8x-24(4-x)=13 | | 3r^2-6r=o | | 8x-11y=-26 | | -3x+6=-3(2x+5) | | -8b+11=83 | | -5x-6=-2x-6 | | -2(5)(-1)(-1)= | | 2v+4=-24 | | 6x+16=8x+8 | | 2z^2+z=15 | | 0.5u+2.9=-0.9u-1.3 | | 16m^4+12m^2n^2+9N^6= | | x-4y=-19 | | -4x+18=-x | | 1/4x=7/2 | | [2x+3]=7 | | -4/5(x-5)=-2/3(x-5) | | -5x=-250 |